Personality and need factors in career aspirations of prospective Nigerian University undergraduates (2000)
This research examined personality and need factors in career aspiration of prospective Nigerian University undergraduates. It identified the career needs of 454 introverted and extroverted secondary school students preparing for Joint Admissions and Matriculation Board (JAMB) examination. Subjects career aspirations, defined as a person's conscious desire, intention and efforts which are aimed at getting involved in a sequence of occupations, jobs and positions in his or her lifetime, cut across 8 different occupational groupings. Personality factors were defined as behavioural attributes or characteristics which an individual is distinctly identified with in some known or unknown degrees and over an enduring period of time. Need factors described those things or benefits which attract a person to aspire to make a certain career. Using partial correlation and Pearson correlation statistics, subjects' responses on career aspiration need questionnaire were analyzed. Results showed a general dominance of money, and popularity needs among subjects in the different occupational grouping Discussion centred on the need for understanding individual and group differences as a way of maximizing organizational productivity and individuals' job satisfaction. The practical implications of the findings for occupational counseling and job placement were also mentioned.